Pengembangan Lembar Kerja Peserta Didik Berbasis Etnopedagogi Melalui Model Project Based Learning Untuk Meningkatkan Kemampuan Menulis Puisi - Sumaryanto Sumaryanto; Hendratno Hendratno; Titik Indarti (LP. Ma'arif Janggan Magetan, 2024)
This research aims to: Find out the process of creating, validity, practicality, and effectiveness of ethnopedagogy-based LKPD through Project Based Learning to improve the ability to write poetry in elementary school students. This LKPD development research refers to the ADDIE model. The research subjects were class V students at SDN Ngampal I with a total of 19 students. The research design uses one group pretest-posttest. The research results show: (1) that the learning device in the form of ATP obtained validation results of 86% and the teaching module obtained validation results of 94%. The results of the validation of the pretest question instrument were 91%. Meanwhile, the LKPD validation results from media experts were 90%. Based on Likert scale calculations, the validation results fall into very feasible criteria. So it can be concluded that the Ethnopedagogy-Based LKPD Using the Project Based Learning Model to Improve the Ability to Write Poetry in Elementary School Students is very suitable for use. (2) There is a moderate increase in obtaining pretest and pretest scores, classically completeness is only 12.5% ​​with a process average of 53.16. The results of the posttest score for classical completeness reached 87.5% with an average posttest score of 81.32. Based on the N-gain score calculation, there is an increase of 0.60 and is included in the criteria for moderate improvement. (3) Observation of students' communication skills obtained results of 86% with 91.8% participation and 94.4% participation. Classically, the average obtained was 92.18, with very active criteria. (4) The results of the teacher's assessment of the Ethnopedagogy-Based LKPD Using the Project Based Learning Model to Improve the Ability to Write Poetry in Elementary School Students obtained a score of 92% and the average result of the student response questionnaire was 96%. From these results, according to the Likert scale calculations which are converted into percentages, they fall into the very good criteria, which means very practical. Thus it can be concluded that the Ethnopedagogy-based LKPD through the Project Based Learning Model to Improve Writing Ability to Write Poetry in Elementary School Students is very practical to use as a learning medium